Volume 6: Materials Technology; C.C. Mei Symposium on Wave Mechanics and Hydrodynamics; Offshore Measurement and Data Interpret 2009
DOI: 10.1115/omae2009-79305
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness Testing Using SENT Specimens in a Sour Environment

Abstract: Offshore pipelines and risers constructed from carbon steel have reduced levels of performance when operating in a sour environment. Fatigue crack growth rates can be significantly higher and material fracture toughness may be significantly lower. In this paper a fracture toughness test procedure for the pipeline girth weld in a sour environment is introduced. The single edge notched tensile (SENT) specimen, which has been widely accepted for the pipeline girth weld fracture toughness tests, was used in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The methodology of testing and application of the fracture toughness value for ECAs of pipeline girth welds for sour service has been presented in a previous OMEA conference (paper OMEA2009-79305 (1) ). During the course of the previous study, the effect of strain rate on the fracture toughness testing result was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology of testing and application of the fracture toughness value for ECAs of pipeline girth welds for sour service has been presented in a previous OMEA conference (paper OMEA2009-79305 (1) ). During the course of the previous study, the effect of strain rate on the fracture toughness testing result was observed.…”
Section: Introductionmentioning
confidence: 99%